(untitled) (Research, Society and Development, 2022)
Biofuels have been occupying space in the fuel market as a renewable substitute for petrol fuels. The thermal and/or thermo-catalytic cracking using triglyceride biomass stands out among the biofuel production processes. Cracking processes result in the production of coke, bio-oil and non-condensable gases. The quantification of each product in a cracking process is directly linked to operational conditions. This project focuses on the use of residual fat from the poultry processing industry, converting it into biofuel so that it can be used in the industry itself as a source of energy. The quality of the products generated are linked to the raw material used, as well as the conditions used in the cracking process. One way to improve the characteristics of the bio-oil produced can be achieved with the use of a catalyst together with thermal cracking. The literature has shown that in thermo-catalytic cracking, there is lower yield in bio-oil, but with some properties, such as acidity and viscosity closer to the value required by legislation for use in engines. This project aims to add value to an industrial waste, by converting this waste into biofuel using thermo-catalytic cracking, with the possibility of being used in the industry itself, as well as investigating the optimization of the process to improve the quality of bio-oil. The yield of the liquid fraction was around 67 % with an acid value of 58.74 mg KOH/g sample.